Calibration and verification of numerical runoff and erosion model - Gabrić Ognjen (Zbornik Radova Građevinskog Fakulteta, 2015)
Based on the field and laboratory measurements, and analogous with development of computational techniques, runoff and erosion models based on equations which describe the physics of the process are also developed. Based on the KINEROS2 model, this paper presents basic modelling principles of runoff and erosion processes based on the St. Venant's equations. Alternative equations for friction calculation, calculation of source and deposition elements and transport capacity are also shown. Numerical models based on original and alternative equations are calibrated and verified on laboratory scale model. According to the results, friction calculation based on the analytic solution of laminar flow must be included in all runoff and erosion models.